Discovery of a novel ligand that modulates the protein–protein interactions of the AAA+ superfamily oncoprotein reptin1. Issue 5 (20th May 2015) - Healy, Alan R.; Houston, Douglas R.; Remnant, Lucy; Huart, Anne-Sophie; Brychtova, Veronika; Maslon, Magda M.; Meers, Olivia; Muller, Petr; Krejci, Adam; Blackburn, Elizabeth A.; Vojtesek, Borek; Hernychova, Lenka; et al.
<x xml:space="preserve">Abstract</x> Discovery and use of a chemical tool.